2016
DOI: 10.3390/en9070564
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Hydraulic Performance in a Solar Air Heater Channel with Multi V-Type Perforated Baffles

Abstract: This article presents heat transfer and fluid flow characteristics in a solar air heater (SAH) channel with multi V-type perforated baffles. The flow passage has an aspect ratio of 10. The relative baffle height, relative pitch, relative baffle hole position, flow attack angle, and baffle open area ratio are 0.6, 8.0, 0.42, 60˝, and 12%, respectively. The Reynolds numbers considered in the study was in the range of 3000-10,000. The re-normalization group (RNG) k-ε turbulence model has been used for numerical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…These correlations, which are used by for the characterization of fluid-flow and heat transfer in ducts [24], are available in the literature [40]: Figures 2(a) and 2(b) show, respectively, a comparison of Nusselt number and friction factor obtained from the present study with those from eqs. (11) and (12). In these figures, the presented results agree reasonably well within ±2.9% and ±5.5% for both friction factor correlation of Blasius and Nusselt number correlation of Dittus-Boelter, respectively.…”
Section: Verification Of Results For a Smooth Channelsupporting
confidence: 82%
See 1 more Smart Citation
“…These correlations, which are used by for the characterization of fluid-flow and heat transfer in ducts [24], are available in the literature [40]: Figures 2(a) and 2(b) show, respectively, a comparison of Nusselt number and friction factor obtained from the present study with those from eqs. (11) and (12). In these figures, the presented results agree reasonably well within ±2.9% and ±5.5% for both friction factor correlation of Blasius and Nusselt number correlation of Dittus-Boelter, respectively.…”
Section: Verification Of Results For a Smooth Channelsupporting
confidence: 82%
“…The shape of baffles is a necessary parameter for the generation of vortices [1][2][3]. Therefore, various shapes have been developed, for example, the V-baffle shape [4][5][6][7][8][9], the W-baffle shape [10], the Z-baffle shape [11], multi V-type perforated baffles [12][13][14][15][16][17] and diamond shape proposed by Sripattanapipat and Promvonge [18]. All these shapes permit an enhancement in the heat transfer rates, but with catastrophic Ppressure drops.…”
Section: Introductionmentioning
confidence: 99%
“…A discrete multi V-pattern rib combined with dimple staggered ribs also had better overall thermal performance compared to other rib shapes. Kumar and Kim [7] reported heat transfer and fluid flow characteristics in a solar air heater channel with multi V-type perforated baffles. The flow passage has an aspect ratio of 10.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that the broken multiple V-type baffles are thermo-hydraulically superior as compared to the other baffles. Kumar and Kim [10] showed that multi V-type perforated baffles performed better as compared to other shapes baffle in a rectangular duct. Karim and Hawlader [11], investigated flat plate, finned and V-corrugated solar air heaters.…”
Section: Introductionmentioning
confidence: 99%